Whither the World Bank and the IMF - Krueger, Anne O. (Journal of Economic Literature, 1997)
This article assesses the possible future directions and roles of the International Monetary Fund and the World Bank. It first reviews their initially envisaged roles at Bretton Woods, and their evolution, concluding that both institutions played valuable roles earlier on. But for both institutions, the world has changed, and the questions as to their future are important. For the IMF, those questions center on its role in providing finance for poor developing countries in balance of payments difficulties and on its role for middle income countries in managing financial crises. For the World Bank, the question is whether it can and should gradually phase out lending for most middle income countries except in times of drastic policy reforms and focus on low-income countries, or whether it should address the soft issues of development.